PENGEMBANGAN PENUNTUN PRAKTIKUM BIOLOGI UMUM BERBASIS INKUIRI TERBIMBING MAHASISWA BIOLOGI STKIP PAYAKUMBUH - Nengsi, Sri (LLDIKTI Wilayah X, 2016)
One of supporting the implementation of the practicum is the practical guidence. To increase motivation, activities, and learning outcomes it is used inquiry based practical guide for students are invited to experiment with doing practical activities with scientific. The purpose of this study was to reveal the validity, practicalities, and guiding the resulting effectiveness of guidence inquiry based on the general biology lesson for students of biology education STKIP Payakumbuh. This research is the development of Plomp development model which consists of three phases: problem identification and needs analysis, design development and implementation, evaluation. The results of this study indicate that the development of practical guidance guided inquiry based general biology for students of biology education STKIP Payakumbuh valid, practically and effectively.